Peran Jalur Rempah dan Dakwah Dalam Perdagangan Maritim Kesultanan Palembang Darussalam dalam Penyebaran Islam (Abad XVI–XIX) - Agus Susilo; Ira Miyarni Sustianingsih; Ratna Wulan Sari; Andriana Sofiarini (LP4MK STKIP PGRI Lubuklinggau, 2026)
The Sultanate of Palembang Darussalam (16th–19th centuries) played an important role as a center of maritime trade as well as a center for the spread of Islam in southern Sumatra. This study aims to analyze how maritime trade activities, especially spices such as pepper and tin, became an effective medium in the process of Islamization in the region. Using an economic and religious history approach, this study examines the symbiotic relationship between economic interests and Islamic proselytizing, as well as the role of the sultanate elite, clerics, and Muslim merchant networks in expanding the influence of Islam. Based on primary sources such as Dutch colonial archives, local chronicles (such as Sedjarah Melaju), and travel notes of foreign travelers, this study shows that Palembang functioned as an “Islamic port city” connecting the Nusantara trade network with the Middle East and India. The port of Palembang was not only a center of commercial transactions, but also a place of cultural and religious exchange. Muslim traders from Arabia, Gujarat, and Malay took advantage of this network to spread the teachings of Islam, while the rulers of Palembang supported it through policies that combined political and religious interests. The research findings reveal that the spread of Islam through Palembang's maritime trade occurred in two forms: (1) Islamization of the elite through political alliances and marriage, and (2) Islamization of the general public through trade interactions and the formation of Muslim communities in port centers. The sultanate also established religious institutions such as mosques and Islamic boarding schools as part of its proselytizing strategy. Thus, this study reinforces the thesis that maritime trade was not only an economic activity, but also a vital instrument in the process of Islamization in the archipelago.